1978
DOI: 10.1152/ajpregu.1978.235.5.r228
|View full text |Cite
|
Sign up to set email alerts
|

Induced hyperthermia in sedated humans and the concept of critical thermal maximum

Abstract: The concept of critical thermal maximum (CTM) has been defined in the literature as the minimal high deep-body temperature that is lethal to an animal. In man the CTM has been estimated at 41.6--42.0 degrees C. Data are presented for sedated, unacclimatized, well-hydrated men heated 1 h at esophageal temperatures of 41.6--42.0 degrees C, without sequelae, except for modest elevation of serum enzymes in two of five patients. These data when combined with other observations in the literature suggest that CTM be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0
2

Year Published

1979
1979
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 0 publications
6
60
0
2
Order By: Relevance
“…Pandolf and Goldman 34) and Mairiaux and Malchaire 35) suggested that the T cr of 39 to 40°C might be taken as the tolerance limits for men at work in hot environment, in view of the critical thermal maximum (i.e., the least high T cr that is lethal to a human being) 36) . The present volunteers surpassed 39°C T cr in most exposures beyond 34.4°C WBGT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pandolf and Goldman 34) and Mairiaux and Malchaire 35) suggested that the T cr of 39 to 40°C might be taken as the tolerance limits for men at work in hot environment, in view of the critical thermal maximum (i.e., the least high T cr that is lethal to a human being) 36) . The present volunteers surpassed 39°C T cr in most exposures beyond 34.4°C WBGT (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Human skin temperature is strongly regulated at 35°C or below under normal conditions, because the skin must be cooler than body core in order for metabolic heat to be conducted to the skin (17). Sustained skin temperatures above 35°C imply elevated core body temperatures (hyperthermia), which reach lethal values (42-43°C) for skin temperatures of 37-38°C even for acclimated and fit individuals (18,19,20,21). We would thus expect sufficiently long periods of T W > 35°C to be intolerable.…”
mentioning
confidence: 99%
“…When endotoxemia can be prevented or tolerated and heat exposure is prolonged, the other pathway of heat stroke can be triggered by the direct thermal effect of heat on tissue cells, causing tissue damage. Heat-induced tissue damage is likely to occur at T c Ͼ 42°C, where proteins begin to denature (8,11). These two pathways of heat stroke are likely to exist in a continuum, with some degree of overlap in their activation (35).…”
mentioning
confidence: 99%